Realización de un documental para sensibilizar a la población urbana de Nueva Loja sobre el manejo adecuado de los desechos sólidos que se producen y su incidencia en el ornato de la ciudad, durante el periodo septiembre – diciembre del 2013 - Cabadiana Guanulema, Víctor Guillermo (2016)
The thesis “a documentary to raise the urban population of Nueva Loja ON SOUND MANAGEMENT OF SOLID WASTE TO BE PRODUCED AND ITS IMPACT ON THE beautification during the period September – December 2013”. The central problem of the research is How to sensitize the urban population of Nueva Loja on the proper management of solid waste produced to maintain adequate beautification? The general objective raised at the beginning of this research was: Designing a media campaign on proper solid waste management, through messages, advertising spots to improve the beautification of the city of Nueva Loja. To achieve real results and objectives, I proceeded to apply the knowledge gained in college, so using the methods: Scientist, Inductive and Deductive Statistical Model. Other tools that resorted within the research field survey were urban population of Nueva Loja and interview the director of Lago Agrio GADM Environment and Head of Communication for how the solid waste management of the city is made. The main results after the research process is: The entire urban population of the city of Nueva Loja, it shows that the municipality does provide the service of garbage collection. The highest percentage of the urban population of Nueva Loja describes the garbage collection service as well. The 100% of the population of Nueva Loja said that the municipality does provide the service of garbage collection. The 74% rate this service as good as it has a budget of $ 15,000 for the proper management of solid waste. Formats have been developed radio, magazine, news, radio spots murals with simple messages aimed at citizens interested in their environment. The GADMLA has a proposal of involvement to all people who recycle trash by hand. The treatment given to solid waste produced by the city are: separation at source (classification of garbage in homes) in the landfill leachate treatment / common waste / hospital waste. There have been three campaigns: Door to door, media awareness and environmental education program with 28 campuses.